INVESTIGATION OF THE IMPLEMENTATION OF PROPHETIC SCHOOL PRINCIPLES MANAGEMENT OF EDUCATIONAL FACILITIES AND INFRASTRUCTURE IN IMPROVING LEARNING SERVICES IN ANNIHAYAH JUNIOR HIGH SCHOOL, RAWAMERTA DISTRICT, KARAWANG DISTRICT - Dadang Rahman Munandar; N Fathurrohman; Yousef Bani Ahmad (Jurnal Scientia, 2023)
The implementation of efficient educational facilities and infrastructure is necessary for the implementation of quality education. Principals play an important role in implementing effective management, which helps improve the educational services provided in schools. The purpose of this study was to analyze the managerial application of prophetic school principals in the implementation of educational facilities and infrastructure in order to improve learning services at Annihayah Middle School, located in Rawamerta District, Karawang Regency. The approach taken by the implementing team consists of providing direction, training, mentoring, and evaluating the client's progress. The conclusion that the Prophet's Principal Managerial Implementation training in the Management of Educational Facilities and Infrastructure was successful can be drawn from the evaluation findings conducted by the community service team. The post test score after the training was held was 91.32%, much higher than the pre test score which was 63.12%. However, due to the limited time available, this training was not without drawbacks, especially in terms of the participants' level of understanding of the subject matter.